MODIFIED HEAT-RESISTANT ZIRCONIA CONCRETE WITH IMPROVED PERFORMANCE CHARACTERISTICS - G. N. Hadjishalapov; A. M. Daitbekov; Y. A. Alkhasova; S. A. Daitbekov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The article deals with methods for preparing modified concrete binders and using as a main component composition of anhydrous sodium silicate binder and a filler zircon concentrate. The physical and technical properties of the heat-resistant binders and concrete, consider various ways to improve the physical and operational characteristics and applications of zircon refractory concretes.